الحمية الغذائية وأثرها على التكفل بأطفال اضطراب التوحد - شرياف, زهرة; شريفي, علي (جامعة الوادي - University of Eloued, 2019)
ملخص: أصبحت عملية التكفل وتأهيل ورعاية الأطفال التوحديين من أولويات الأولياء والأخصائيين والباحثين في هذا المجال، حيث أدى الاهتمام بالبحث عن علاج فعال لهذه الفئة إلى ظهور العديد من البرامج والعلاجات متنوعة الأشكال والأساليب التي تهدف إلى التخفيف من مظاهر العجز وتحسين نوعية الحياة والارتقاء بالاستقلال الوظيفي والاجتماعي للأطفال المصابين بالتوحد. ونؤكد في هذا المقال على فعالية العلاج بالحمية الغذائية الذي تؤدي دورا فعالا في مساعدة المصابين باضطراب التوحد في تخفيف الكثير من أعراض التوحد وحدته.Abstract: The process of sponsoring, rehabilitating and caring for autistic children has become a priority for parents, specialists and researchers in this field. The interest in the search for effective treatment for this group has led to the emergence of many programs and treatments of various forms and methods aimed at alleviating the manifestations of disability and improve the quality of life and improve the functional and social independence of children with autism. We emphasize in this article on the effectiveness of diet therapy, which plays an effective role in helping people with autism in alleviating many of the symptoms and severity of autism.
مقال
Keywords: العلاج الحمية الغذائية؛ أطفال ذوي اضطراب التوحد؛ التكفل.: Dietary Treatment; children with autism spectrum disorder; adjustment